Identifikasi Indeks Kelayakan Obyek Wisata Alam Pantai Alombango dengan Pendekatan 4 A (Atracction, Accessibility, Amenity, dan Ancillary) - Bulan Suci Ramadhani; Indriani Umar (Yayasan Literasi Sains Indonesia, 2024)
The feasibility of tourism objects is important to be identified to assist in proper development planning, support local economic growth, and plan for sustainable use of resources. Alombango Beach is one of the natural tourist attractions located in Pohuwato Regency. The Alombango Beach Tourism Object has a beautiful natural charm, still natural, clean and far from the hustle and bustle of tourists because its existence is not known by the wider community, especially for prospective tourists outside the region. In its development, there are problems in the provision of facilities that are not optimal. This study aims to identify the feasibility of Alombango Beach Natural Tourism Objects with a 4 A approach (Attraction, Accessibility, Amenity and Ancillary). The approach used is mix methods. The research variables are in the form of aspects of attractions, accessibility, facilities, and service institutions (Ancillary). The results of the study show that the elements of Attraction and Accessibility have an index of 83.33% and 80%, which means that they are in the category of high index or suitable for development. Meanwhile, the amenity and ancillary elements have an index of 66.66%, which means that they are in the category of medium or not yet suitable for development. The researcher hopes that the results of this study can be used as a reference in efforts to improve existing shortcomings so that the Alombango Beach Tourism Object can be more optimal in providing a satisfactory experience for tourists who visit, thereby contributing to supporting economic growth and sustainable tourism development.